2015
DOI: 10.1503/cmaj.150535
|View full text |Cite
|
Sign up to set email alerts
|

Resting heart rate and all-cause and cardiovascular mortality in the general population: a meta-analysis

Abstract: Interpretation: Higher resting heart rate was independently associated with increased risks of all-cause and cardiovascular mortality. This indicates that resting heart rate is a predictor of all-cause and cardiovascular mortality in the general population. Abstract Research E54CMAJ, February 16, 2016, 188(3) traditional risk factors of cardiovascular disease on the association of resting heart rate with risk of all-cause and cardiovascular mortality. Methods Literature search and selectionWe searched PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
178
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(206 citation statements)
references
References 74 publications
17
178
1
10
Order By: Relevance
“…Compared with 70 beats/min, a linear dose-response analysis indicated a significantly protective effect of lower resting heart rates on the risk of all-cause mortality in general populations in our previous study. 6 The results of the current meta-analysis showed that, compared with 70 beats/min, lower resting heart rate was also associated with a significantly decreased risk of mortality from noncardio vascular diseases. These findings indicate the possibility that "the slower the heart rate, the better" 58 for all-cause mortality and mortality from noncardiovascular diseases in general populations.…”
Section: (M)mentioning
confidence: 69%
See 2 more Smart Citations
“…Compared with 70 beats/min, a linear dose-response analysis indicated a significantly protective effect of lower resting heart rates on the risk of all-cause mortality in general populations in our previous study. 6 The results of the current meta-analysis showed that, compared with 70 beats/min, lower resting heart rate was also associated with a significantly decreased risk of mortality from noncardio vascular diseases. These findings indicate the possibility that "the slower the heart rate, the better" 58 for all-cause mortality and mortality from noncardiovascular diseases in general populations.…”
Section: (M)mentioning
confidence: 69%
“…6 In brief, we combined study-specific logarithms of RRs for an increment of 10 beats/min in resting heart rate using a random-effects model. We used the I 2 statistic to evaluate between-study hetero geneity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Связь между ЧСС покоя и риском общей и сердечно-сосудистой (СС) смертности исследовалась за последние четверть века во многих эпидемиологических и популяци-онных исследованиях, причем как у лиц без СС патологии, так и у пациентов с различными заболеваниями сердца [28][29][30][31]. Общим выводом абсолютно всех исследований можно считать наличие прямой связи между повышением ЧСС и увеличением риска смерти.…”
Section: обзоры §unclassified
“…Более сложным явля-ется ответ на вопрос: какова оптимальная ЧСС покоя? Для здоровых лиц, как это было показано во французском регистре, повышение риска смерти начинается с ЧСС более 55-60 уд / мин [30][31][32]. Аналогичные результаты были получены и при исследовании пациентов с дока-занной коронарной болезнью сердца [33] и перенесших острый ИМ [34].…”
Section: обзоры §unclassified